Deliverable 3.15 Final implementation and data: Distributed systems for atmosphere and land - Goeckede, Mathias; Domine, Florent; Oechel, Walter; Pirazzini, Roberta; Sachs, Torsten; Tjernström, Michael; Zona, Donatella (Zenodo, 2021)
This document describes the work conducted within INTAROS Task 3.5. This task comprises contributions from seven different partners, operating novel terrestrial or atmospheric observations across different methodological and geographical areas in the Arctic. This document is intended to: − Demonstrate that all partners delivered their results/products according to the requirements listed in the description of work, − Summarize changes in the work plan in the context of COVID-19 related problems, mostly linked to travel restrictions and inaccessibility of field sites. These issues reduced the findings that can be reported here, however, without substantially compromising the overarching objectives, − Describe, on a activity-by-activity level, the novel observations implemented by each partner, the datasets obtained, and their suitability for continuous, long-term operations in an improved future Arctic observing system, − Document the ‘lessons learned’ while designing, installing and operating the novel observation techniques, − Provide a concise interpretation of the specific datasets that were obtained within Task 3.5 observational campaigns, − Summarize data availability, including links to publicly accessible repositories where data can be retrieved by the scientific community, − Give an outlook on plans and options regarding the future operation of the specific observation systems.